THE PERCEPTION OF ACADEMIC CYBER PLAGIARISM BY TRANSLATION STUDENTS AT THE INTERNATIONAL UNIVERSITY OF VALENCIA (VIU) - Gallent Torres, Cinta (2017)
This paper presents the results of a research work carried out on cyber-plagiarism in university online language teaching and translation training. Following a theoretical review of cyber-plagiarism and an analysis of the reasons behind this phenomenon in education, an ad hoc survey was conducted on students in the first courses of the Translation and Interpretation degree at the International University of Valencia (VIU). The purpose of this instrument was to analyze how students use other people’s intellectual property to develop their own academic activities. From the results obtained, students (n=73) still do not have a clear idea of how and when to reference their sources. Moreover, they need some training to ensure they reference correctly. Occasionally, they do not cyber-plagiarize deliberately, but involuntarily, as they are unaware that they are doing it. They do not know the real limitation of the concept, the institution’s rules concerning cyber-plagiarism, and the penalties to be applied in each case. Therefore, it is necessary to take urgent actions to teach students the importance of making an honest use of the information available on the internet, as well as to develop the students’ informational competence, enabling them to transform the information they use into knowledge.